Women's Roles and Conflicts in Divakaruni's Arranged Marriage - Zakiyatul Mufidah; Miftahur Roifah (IAIN MADURA, 2020)
The cases of women experiencing gender-biased, injustice, abuse, and violence do not only exist in stories of literary works but it does exist in real life as we believe that literary text is the reflection of the real life. In addition, feminism is more likely concerning the division of gender roles and its implication to the women's life to be academically worth it. This study is intended to identify what kind of women's roles and conflicts are portrayed in literary works and to explain how women's roles and conflicts are reflected through literary text. This study is a qualitative study which applies close reading in finding the data. The results of the study show that the roles of women in Divakaruni’s Arranged Marriage are mainly aiming at fulfilling the domestic affairs. While, two conflicts are faced by the women; domestic violence and psychological pressures by their husbands and family. In addition, it also indicates that most women are still prevalent to destiny as housewives and to serve their husband’s needs.